Spleen-preserving distal pancreatectomy with splenic vessel preservation: challenges in measuring the learning curve - Blair, Alex B.; Sham, Jonathan G. (Laparoscopic Surgery, 2018)
Laparoscopy developed in the late 20th century with the aim of decreasing procedural invasiveness and improving patient outcomes. Multiple studies have demonstrated the utility of minimally invasive approaches in decreasing blood loss, shortening length of hospital stay, improving postoperative pain and lowering rates of surgical site infections (1,2).